(untitled) (Journal of Laboratory Animal Science, 2025)
This study investigated the quality of treated reverse osmosis drinking water in a specific pathogen free rodent facility. The water bottles placed in the animal rooms were evaluated on days 10, 14, and 21 for room-level assessment. For cage-level assessment, the water was stored for 14 days inside the room and then evaluated on days 2 and 5 (group A – 5 mice) and days 2, 5, 7, 9, and 14 (group B – 2 mice) after provision to the mice in individually ventilated cages. At the room level, a significant decrease in free chlorine was observed from days 10 to 21 (p<0.0001). The concentrations of heterotrophic bacteria and Pseudomonas aeruginosa were consistently low (<1 CFU/mL and <1 CFU/100 mL, respectively). Cagelevel assessment revealed a significant decrease in free chlorine at days 7 (p = 0.0291) and 14 (p = 0.0231) for Group B. Adenosine triphosphate was detected on days 2 and 5 (Group A) and days 5, 7, 9, and 14 (Group B). Heterotrophic bacteria were found in Group A, day 5 (460 CFU/mL), and Group B, days 9 (2 CFU/mL) and 14 (2000 CFU/mL). The level of Pseudomonas aeruginosa remained low in both groups. There was no significant change in the pH at the room or cage level. The findings suggest that water bottles filled with treated reverse osmosis water can be stored unused in rooms for 14 days before being distributed to cages with at most two animals for 7 days. For higher stocking densities, it is recommended to change water bottles every two days.